Combating copyright piracy: A Malaysian perspective - Tay, P.S. (2008)
During th,e era of analog technology, musical works were stored by encoding the works in a physical medium, such as music cassettes, videotapes, vinyl records and other forms of magnetic tapes. Reproduction of any musical work from those media would result in deterioration in quality of the reproduced music. This was a direct result of the inherent nature of analog technology. At that time, music piracy, which typically took the form of the unauthorized reproduction of music into records or cassettes which were then illegally sold for commercial gains, was a phenomenon which was not as serious as it is today. The deterioration in quality upon subsequent reproductions of analog works and the limitations of reproduction equipment served as a natural obstacle to widespread music piracy. All these were to change with the advent of digital technology, which allowed the means of reproducing an unlimited number of perfect copies very speedily, without any loss (n the quality of the reproduced music. CD and DVD burners became a common feature and contributed to the incidence of music piracy. At the same time, further developments in digital technology and the Internet have made it possible for Internet users to access, reproduce and store Internet contents. The music industry is currently undermined by the availability of file sharing of music services over the Internet using peer-to-peer technology. Peer-to-peer technology enables Internet users to exchange fifes with each other directly or through an intermediary server. In the light of the current serious state of music piracy worldwide and, also, in Malaysia, this paper examines the legal weapons which are available in Malaysia to combat music piracy, both in the physical and digital world. It also discusses the efforts of the Malaysian Government and music organizations in the country to curb the incidence of music piracy.